Mato Grosso: as razões de um desastre: defesa imperial e ocupação paraguaia na fronteira oeste do Brasil durante a Guerra da Tríplice Aliança (1864-1870) - Miranda Filho, Orlando de (2016)
During the 19th century, a long series of international disputes created tensions in the La Plata Basin, triggering multiple conflicts betwe en nation states that were going through a consolidation process. Among the most frequent disputes there were: handled navigation agreements; territorial claims; different governance models; hegemonic intentions and struggle for political and economic sove reignty of platino governments. Our research focused on the study of the origins of the War of the Triple Alliance (1864 1870), more specifically on the Paraguayan occupation of the imperial west. Located in a border area, the province of Mato Grosso house d disputed areas since the colonial era. Inhabited by several native groups, the Pantanal region received strong settler influx when the bandeirantes led by Pascoal Moreira Cabral found gold nuggets in the banks of Coxipó Mirim River in 1719. This discover y led the Portuguese monarchy to create the captaincy of Mato Grosso in 1748, giving rise to repeated questions about the limits of the local border. The Luso Brazilians, facing protest from the Spanish (in the colonial period) and from Paraguay (after the independence in 1811), sought to control that vast area of rivers which integrated the bacia platina and guaranteed important trade and communication with the Southern Cone and the rest of Brazil. In 1864, on the eve of the War of the Triple Alliance, the Paraguayans thought themselves to be the rightful owners of a strip of land between the Apa and White rivers, located in the south of the Mato Grosso province occupied during the mining expansion of the 18th century, which generated questions to the imper ial about the lack of treaties to solve the dispute. But the scene was much broader. In December 1864, when Francisco Solano López, the Paraguayan President, ordered the South Mato Grosso invasion, there was a complex international political architecture. The territorial dispute was part of the origins of the war, but it can not be thought of as a simple expansion of Paraguay to avoid reproducing insufficient explanations of the national patriotic historiography. The province of Mato Grosso, while waiting f or the war, was not prepared for it. With a dispersed population and a high officialdom unwilling to fight, escape prevailed in confronting the Paraguayans. The results of the quick victories of lopistas troops during the occupation, and the systematic imp erial defections proved to be insufficient actions taken by political leaders and the military in Mato Grosso.